SISFOSPEM (Information System of Supervision, Reporting, Evaluation and Monitoring) East Java Regional Work Council (International Journal of Scientific Research and Management (IJSRM), 2022)
In collecting data on the work program reports of the East Java Branch Work Councils, the East Java Regional Work Councils obtain data from forms sent via email to each branch. In 2020, supervision was carried out by sending SPEM instruments via google forms, in which data collection and the data have been recording manually via excel. That data collection and report task are very ineffective because it takes a long time to collect and sort the data. In order to overcome the problems, a SPEM information system is needed as a medium for delivering information as well as supervising, reporting, evaluating, and monitoring the Branch Work Councils throughout East Java. In making this information system, we use the waterfall research methodology, where there are six stages of the system design process: problem identification, system requirements analysis, system design, system creation, system testing, and research analysis results. The result of this research is a SPEM information system. Furthermore, the test results using black-box testing state that the information system of SPEM that has been created can run well according to the expected criteria. The testing results using user acceptance testing with 18 respondents from the East Java Regional Work Council and 20 respondents from the Branch Work Council throughout East Java, stated that the SPEM information system is easy to use. This system is beneficial for users and organizations.